Economic Behavior under Alcohol Influence: An Experiment on Time, Risk, and Social Preferences - Luca Corazzini; Antonio Filippin; Paolo Vanin (Institute for the Study of Labor (IZA), 2014)
We report results from an incentivized laboratory experiment to provide controlled evidence on the causal effects of alcohol consumption on risk preferences, time perception and altruism. Our design allows disentangling the pharmacological effects of alcohol intoxication from those mediated by expectations, as we compare behaviors of three groups of subjects: those participating to an experiment with no reference to alcohol, those exposed to the possibility of consuming alcohol but assigned to a placebo and those having effectively consumed alcohol. Once randomly assigned to one treatment, subjects were administered a series of consecutive economic tasks, being the sequence kept constant across treatments. After controlling for both the willingness to pay and the potential misperception of probabilities as elicited in the experiment, we do not detect any effect of alcohol in depleting subjects' risk tolerance. On the contrary, we find that alcohol intoxication increases impatience. Moreover, we find that alcohol makes subjects less generous as we detect a negative relationship between the blood alcohol concentration and the amount of money donated to NGOs.
Keywords: D03; I10; C91; 330; alcohol; risk preferences; impatience; laboratory experiment